(untitled) (Bunayya : Jurnal Pendidikan Anak, 2025)
This study arises from the fact that religious moderation values are not yet explicitly integrated into Early Childhood Education (ECE) School Curriculum (KSP) documents in Lampung, despite strong national regulations on strengthening religious moderation. The main objective is to develop a religious-moderation-based KSP guideline for ECE institutions to serve as a reference for curriculum development. The research employed a Research and Development (R&D) method using the Borg & Gall model, including needs analysis, design, expert validation, revision, limited trial, and large-scale trial. The study produced a KSP guideline module that organizes and plans learning based on indicators and values of religious moderation. Expert validation from three validators yielded an average feasibility of 90% (very feasible). At the same time, trials with teachers and principals indicated that the guideline is understandable, practical, and effective for integrating religious moderation into KSP.